2020
DOI: 10.1186/s12961-020-00586-w
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for health economics research and practice in Jordan, Lebanon, the occupied Palestinian territories and Turkey: needs assessment and options for development

Abstract: Background: Capacity for health economics analysis and research is indispensable for evidence-informed allocations of scarce health resources; however, little is known about the experience and capacity strengthening preferences of academics and practitioners in the Eastern Mediterranean region. This study aimed to assess the needs for strengthening health economics capacity in Jordan, Lebanon, the occupied Palestinian territories and Turkey as part of the Research for Health in Conflict in the Middle East and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…To minimize bias introduced by manual selection, we employed a well-defined selection criteria, taking Gheorghe and colleagues’ research as a reference. Specifically, we included documents that explicitly listed any economic outcome related to health, disease, or disability, including but not limited to cost, cost-effectiveness, patient-reported outcomes, poverty associated with accessing healthcare, provider or health system performance, and health expenditures, in the abstract or title 29 . The study selection and flow chart of the research framework are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…To minimize bias introduced by manual selection, we employed a well-defined selection criteria, taking Gheorghe and colleagues’ research as a reference. Specifically, we included documents that explicitly listed any economic outcome related to health, disease, or disability, including but not limited to cost, cost-effectiveness, patient-reported outcomes, poverty associated with accessing healthcare, provider or health system performance, and health expenditures, in the abstract or title 29 . The study selection and flow chart of the research framework are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The ethics and patient and public involvement sub-sections contain three and four statements each. In the fourth, and last sub-section informants are asked about their skills in health economics (11 statements); these statements were adapted (with permission) from the iDSI economic tool [ 30 ]. Each statement seeks informants to reflect and respond with what the individual knows about topic and what level of skills she/he has in the area.…”
Section: Methodsmentioning
confidence: 99%
“…The team was not aware of any existing validated tools for this purpose, and tools that we were aware of, were for example the “WHO Global Survey on Health Technology Assessment by National Authorities” [ 29 ], which focused on system level or institutional capacities for HTA, rather than the individual which was necessary for NIPH’s long-term collaborations. Other tools the team was aware of focused only on health economics [ 30 ] or patient and public engagement [ 31 ]. In addition, a summary report of published literature related to capacity building and HTA in Ghana had identified strength in primary research, information retrieval, and analysis [ 13 ], but that no specific assessment HTA assessment had previously been completed in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…10 Türkiye'de sağlık ekonomisi alanı son yıllarda önemli ölçüde genişlemiş olup, bilimsel dergilerde yayımlanan ekonomik değerlendirme içeren yayınların sayısı da bu durumu yansıtmaktadır. 11 Ancak çalışmalar, Türkçe bir raporlama kılavuzu olmaması nedeniyle tutarsız bir şekilde sunulmaktadır. 12 Türkiye'de ilk STD ajansı Sağlık Bakanlığı (SB) tarafından yaklaşık 10 yıl önce kurulmuştur.…”
unclassified